Optimization of Traffic Dikmas Counseling by the Kamsel Unit to Prevent Traffic Accidents in the Jurisdiction of the Klaten Police - Bayu Aji Santoso (Advances in Police Science Research Journal, 2024)
The increase in the number of vehicles in Central Java Province has caused serious problems. In driving, many people still do not know how to drive properly and correctly so that there is an increase in traffic accidents. Therefore, to reduce the number of traffic accidents, police personnel play a role in providing traffic understanding to the public. The purpose of writing this assignment is to describe the Kamsel Unit's organizational resources, implementation, and factors that influence the implementation of Dikmas through outreach activities by the Kamsel Unit to prevent accidents in the jurisdiction of the Klaten Police. The method used is field research which combines observation techniques, interviews and document studies as materials for obtaining information in this writing. From this writing activity, it can be concluded that there are three things that need to be considered to optimize community education through outreach activities by the Kamsel Unit to prevent accidents in the jurisdiction of the Klaten Police. The first, namely the management of the implementation of community education using the extension method can be optimal if it is carried out in 4 (four) stages based on management theory without overriding the instructions of the Chief of Police in the Implementation Guidelines for the Chief of Police No Pol: Juklak/05/V/2003 concerning education for the traffic community. Second, the implementation of Dikmas counseling will then be optimal if the Kamsel unit can optimize the existing supporting factors and can anticipate the inhibiting factors and not make them an obstacle. Third, the organizational resources of the South Kamal Unit in carrying out community education counseling to the public in order to prevent traffic accidents in the jurisdiction of the Klaten Police are still not optimal.